Positron emission tomography assessment of large vessel inflammation in patients with newly diagnosed, biopsy-proven giant cell arteritis: a prospective, case–control study. Issue 7 (24th March 2014) - Prieto-González, Sergio; Depetris, Marina; García-Martínez, Ana; Espígol-Frigolé, Georgina; Tavera-Bahillo, Itziar; Corbera-Bellata, Marc; Planas-Rigol, Ester; Alba, Marco A; Hernández-Rodríguez, José; Grau, Josep M; Lomeña, Franciso; Cid, Maria C
Abstract : Background: Positron emission tomography (PET) scan is emerging as a promising imaging technique to detect large-vessel inflammation in giant cell arteritis (GCA). However, the lack of a standardised definition of arteritis based on 18 fluorodeoxyglucose (FDG) uptake is an important limitation to the use of PET scan for diagnostic purposes. Objective: To prospectively assess the intensity and distribution of FDG uptake at different vascular territories in patients with newly diagnosed GCA compared with controls. Methods: 32 consecutive, biopsy-proven, GCA patients treated with glucocorticoids for ≤3 days were included. The control group consisted of 20 individuals, who underwent PET/CT for cancer staging. Maximal standardised uptake value (SUVm) was calculated at four aortic segments, supraaortic branches and iliac-femoral territory. Sensitivity and specificity was calculated by receiver–operator characteristic curves (ROC) analysis. Results: Mean SUVm was significantly higher in patients than in controls in all vessels explored and correlated with acute-phase reactants and serum IL-6. Mean of the SUVm at all the vascular territories had an area under the curve (AUC) of 0.830, and a cut-off of 1.89 yielded a sensitivity of 80% and a specificity of 79% for GCA diagnosis. There were no significant differences in AUC among the vascular beds examined. Conclusions: FDG uptake by large vessels has a substantial sensitivity and specificity for GCA diagnosis.